2016
DOI: 10.1021/acs.est.6b03301
|View full text |Cite
|
Sign up to set email alerts
|

Linking Oxidative Stress and Magnitude of Compensatory Responses with Life-Stage Specific Differences in Sensitivity of White Sturgeon (Acipenser transmontanus) to Copper or Cadmium

Abstract: Sensitivity of white sturgeon (Acipenser transmontanus) to copper (Cu) or cadmium (Cd) has been shown to significantly differ as a function of life-stage. This study investigated oxidative stress, metal homeostasis, and associated compensatory responses as potential mechanisms of this sensitivity pattern in three early life-stages. Sturgeon were most sensitive to Cu at 15 days post hatch (dph), which was accompanied by a significant increase in lipid peroxidation (LPO). Genes involved with amelioration of oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…These effects have been documented in fish collected from metal‐contaminated sites and following exposure to Cu in the laboratory. For example, Tang et al (2016) documented elevated lipid peroxidation products in 15 dph white sturgeon exposed to 10 µg/L Cu in background water similar in composition to the Columbia River water. Similarly, elevated lipid peroxidation (oxidative stress), metallothionein increase, and tissue lesions were associated with trace metals in resident trout collected from a mining site with increased concentrations of Cu, Cd, Pb, and Zn (Farag et al 1995).…”
Section: Resultsmentioning
confidence: 99%
“…These effects have been documented in fish collected from metal‐contaminated sites and following exposure to Cu in the laboratory. For example, Tang et al (2016) documented elevated lipid peroxidation products in 15 dph white sturgeon exposed to 10 µg/L Cu in background water similar in composition to the Columbia River water. Similarly, elevated lipid peroxidation (oxidative stress), metallothionein increase, and tissue lesions were associated with trace metals in resident trout collected from a mining site with increased concentrations of Cu, Cd, Pb, and Zn (Farag et al 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to heavy metals triggers several adaptive responses, among which the induction of metal-binding proteins (MTs) involved in both transport and detoxification of metals. Stage-specific differences in the implementation of compensatory responses have been discussed several times in fish exposed to heavy metals [59]. Osman and colleagues [67] showed no significant differences in MTs' expression after exposure to high lead concentrations in embryonic tissues of African catfish (Clarias gariepinus), suggesting that high sensitivity during early stages may be due to the failure of homeostatic mechanisms.…”
Section: Gene-expressionmentioning
confidence: 99%
“…On the contrary, the significant increase in mtf observed here clearly indicates zebrafish embryos and larvae's ability to mount an adaptive response to lead injuries. According to Tang et al [59], the differential activation of homeostatic mechanisms, including MT induction, may be responsible for species-specific and stage-specific differences in metal sensitivity observed in fishes. Besides, several studies reported that MTs significantly contribute to protecting the organism from oxidative stress acting as scavenging against free oxygen radicals [60][61][62].…”
Section: Gene-expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of oxygen (O2) is essentially an electron acceptor so that it will receive free electrons even when it reaches stability, thus forming superoxide (O2.-) these free radicals which bind with oxygen are called Reactive Oxygen Species (ROS), X + + Y-X. + Y: (The process of occurring oxygen species) [37], [40].…”
Section: Heavy Metal Induced Oxidative Stressmentioning
confidence: 99%